Prediction of seed storability of Jatropha curcas through accelerated ageing test - Gurunathan, N.; Srimathi, P.; Venkatesh, A. (Indian Journal of Agroforestry, 2020)
The study on prediction of seed storability was conducted in accelerated ageing chamber for the biofuel crop Jatropha curcas. It is revealed that the seed quality characters decreased with advances in ageing and the seeds lost their germination within 9 days indicating Jatropha curcas as a medium storer. There was a little varaiation in storagebehaviour of different seed sources.Â